Sex estimation by femur in modern Thai population - Monum T. (2017)
© Società Editrice Universo (SEU). Sex estimation is an important step of postmortem investigation and the femur is a useful bone for sex estimation by using metric analysis method. Even though there have been a reported sex estimation method by using femur in Thais, the temporal change related to time and anthropological data need to be renewed. Thus the aim of this study is to re-evaluate sex estimation by femur in Thais. 97 adult male and 103 female femora were random chosen from Forensic osteology research center and 6 measurements were applied tend to. To compare with previous Thai data, mid shaft diameter to increase but femoral head and epicondylar breadth to stabilize and when tested previous discriminant function by vertical head diameter and epicondalar breadth, the accuracy of prediction was lower than previous report. From the new data, epicondalar breadth is the best variable for distinguishing male and female at 88.7 percent of accuracy, following by transverse and vertical head diameter at 86.7 percent and femoral neck diameter at 81.7 percent of accuracy. Multivariate discriminant analysis indicated transverse head diameter and epicondylar breadth performed highest rate of accuracy at 89.7 percent. The percent of accuracy of femur was close to previous reported sex estimation by talus and calcaneus in Thai population. Thus, for especially in case of lower limb remain, which absence of pelvis.